Broodstock Health Management for Cantang Grouper (Epinephelus sp.) in BBRBLPP Gondol Bali - Muh Sulaiman Dadiono; Maheno Sri Widodo; Rudy Wijaya (Universitas Tidar, 2020)
Fish health is an important problem faced by Cantang grouper (Ephinephelus sp.) Hatcheries. Broodstock health management needs to be managed properly so as not to decrease the quality and production of Cantang grouper seeds. Cantang grouper broodstock health management includes the process of maintaining grouper broodstock, feeding, disease control and water quality management. The data collection method is done by recording the results of active participation, interviews and observations. Broodstock grouper cantang are maintained in ponds made of concrete with sizes ranging from 150 meter kibik and a depth of 3 meter. Pond cleaning is carried out once or twice a month with the addition of 2 kg of chlorine / 150 tons of water. Grouper broodstock is fed 10 kg for 24 broodstock. feed in the form of trash fish, squid, mackarel, vitamin C and vitamin E. The types of diseases that often attack grouper broodstock are Criptocaryon irritans, Benedia sp and Vibrio alginolyticus. Water quality parameters measured in grouper broodstock ponds are salinity and temperature. The water salinity in broodstock ponds ranges from 34 - 35 ppt and temperatures range from 27-31 derajat celcius.